2015
DOI: 10.3389/fonc.2015.00003
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-Induced Epithelial–Mesenchymal Transition Promotes Monocyte/Macrophage Properties in Breast Cancer Cells

Abstract: Breast cancer progression toward metastatic disease is linked to re-activation of epithelial–mesenchymal transition (EMT), a latent developmental process. Breast cancer cells undergoing EMT lose epithelial characteristics and gain the capacity to invade the surrounding tissue and migrate away from the primary tumor. However, less is known about the possible role of EMT in providing cancer cells with properties that allow them to traffic to distant sites. Given the fact that pro-metastatic cancer cells share a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 68 publications
3
42
0
1
Order By: Relevance
“…Although the expression levels of Cdh1 and another epithelial gene, Esrp2 , were not significantly decreased by 48-h treatment with TGF-β in EpRas cells, and the expression level of Cdh1 was even increased by TGF-β in EpH4 cells, we found enhanced down-regulation of Cdh1 and Esrp2 by prolonged culture of EpRas cells with TGF-β (8 days, Supplementary Fig. S1), suggesting continued alteration of transcriptional program by long-term stimulation, as previously described 26 .
Figure 1Regulation of accessible chromatin regions (FAIRE-positive regions) by TGF-β at EMT-related gene loci in EpH4 and EpRas cells. ( A ) Expression levels of Cdh2 (encoding N-cadherin), Fn1 (encoding fibronectin), Cdh1 (encoding E-cadherin), and Esrp2 mRNA evaluated by RNA-seq.
…”
Section: Resultssupporting
confidence: 85%
“…Although the expression levels of Cdh1 and another epithelial gene, Esrp2 , were not significantly decreased by 48-h treatment with TGF-β in EpRas cells, and the expression level of Cdh1 was even increased by TGF-β in EpH4 cells, we found enhanced down-regulation of Cdh1 and Esrp2 by prolonged culture of EpRas cells with TGF-β (8 days, Supplementary Fig. S1), suggesting continued alteration of transcriptional program by long-term stimulation, as previously described 26 .
Figure 1Regulation of accessible chromatin regions (FAIRE-positive regions) by TGF-β at EMT-related gene loci in EpH4 and EpRas cells. ( A ) Expression levels of Cdh2 (encoding N-cadherin), Fn1 (encoding fibronectin), Cdh1 (encoding E-cadherin), and Esrp2 mRNA evaluated by RNA-seq.
…”
Section: Resultssupporting
confidence: 85%
“…Considering the possibility that cancer cells undergoing EMT may acquire additional properties of immune cells, we performed gene profiling analysis of breast cancer cells that had been allowed to adopt an EMT program after treatment with TGF-b for 2 weeks. Intriguingly, a cluster of genes, which are normally expressed in myeloid type of immune cells including macrophages and DCs, were induced in the EMT cells (Johansson et al, 2015). These genes encode proteins with variable intracellular localization and molecular function, and while some of them previously have been linked to cancer metastasis, others have not.…”
Section: Emt Cells Hijack the Immune System To Disseminate Through Thmentioning
confidence: 99%
“…Additionally, we observed that induction of RASSF10 by TGFβ vs. mock was highest under low cellular density (Figure 2f), which was accompanied by the phenotypical spindle like morphology and upregulation of SNAI2 [30]. We also observed that TGFβ treatment of A549 cells for two days led to an upregulation of RASSF10 and long-term TGFβ exposure (six days), when cells adopted an EMT program [31], caused an inhibition of RASSF10 expression ( Figure 2h). Consistently, short-term TGFβ treatment led to cell cycle arrest at phase G1-G0 as measured by flow cytometry (Figure 2i) in accordance with earlier results [32].…”
Section: Rassf10 Is Induced By the Emt Driver Tgfβ And Rassf10 Depletmentioning
confidence: 67%